Brain arteriovenous malformation involving a persistent primitive olfactory artery - Ideguchi, Minoru; Kim, Kyongsong; Kominami, Shushi; Morita, Akio (Nepal Journal of Neuroscience, 2022)
The incidence of a persistent primitive olfactory artery is extremely rare. This anomaly may be involved in the development of aneurysms due to hemodynamic stress. We report a patient with a brain arteriovenous malformation mainly fed by a persistent primitive olfactory artery. A 40-year-old healthy man experienced transient numbness around the left side of his mouth. Magnetic resonance imaging incidentally disclosed flow voids inside and at the medial part of the pre-central gyrus of the left frontal lobe with dilation of the cortical veins. A left internal carotid artery angiogram revealed that a left persistent primitive olfactory artery with a proximal hair-pin turn fed an anterior component of the nidus. A right internal carotid artery angiogram showed that the right bihemispheric anterior cerebral artery fed a posterior component of the nidus. There was no aneurysm in the nidus or on the feeding vessel. The diagnosis was asymptomatic arteriovenous malformation (Spetzler-Martin grade 3). The patient developed systemic exanthema with facial edema after diagnostic angiography. We ruled out target embolization followed by stereotactic radiosurgery and placed him under close conservative outpatient observation. We suspect that the arteriovenous malformation was due to the presence of a pre-exiting persistent primitive olfactory artery. In patients with a persistent primitive olfactory artery, structural fragility and hemodynamic stress may elicit aneurysms at the apex of the hairpin curve of the persistent primitive olfactory artery.